2005
DOI: 10.1007/bf03327554
|View full text |Cite
|
Sign up to set email alerts
|

Differences in diet composition of Brazilian adolescent girls with positive or negative score in the Eating Attitudes Test

Abstract: Dieting, a behavioral phenomenon which is becoming more frequent among adolescents, is certainly involved in the pathogenesis of eating disorders, especially anorexia nervosa (AN), and may result in an unbalanced nutrition. Our study aimed at identifying girls with symptoms of AN and describing their diets. We assessed girls with symptoms by using the Eating Attitudes Test and considered girls with a score > or = 20 as having symptoms of AN. To evaluate their diets, a "modified" 24-hour recall was applied on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
18
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 28 publications
9
18
0
1
Order By: Relevance
“…In this regard, and in line with the findings of several authors (9)(10)(11) , our study showed lower energy and/ or macronutrient intake(s) in adolescent females at rED.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this regard, and in line with the findings of several authors (9)(10)(11) , our study showed lower energy and/ or macronutrient intake(s) in adolescent females at rED.…”
Section: Discussionsupporting
confidence: 93%
“…Lower intakes of Na, Fe and vitamins B 12 , B 6 , A, E and/or C have been observed in females at rED (9)(10)(11)(12) . Compared with these studies, our results show lower intakes of a greater number of micronutrients (Ca, Fe, Mg, K, P, Na, thiamin, vitamins E, C, B 6 , B 12 , pantothenic acid and folic acid) in adolescents at rED and with EDNOS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estudos internacionais que avaliaram comportamento de risco encontraram frequências variando de 6,2% na China 9 a 21,7% no Paquistão 10 . Os estudos nacionais sobre comportamento de risco para TA no Brasil foram localizados e realizados com amostras pequenas e variadas -como escolares, adolescentes e estudantes universitá-rias [13][14][15][16][17][18] . Nenhum estudo foi realizado até o momento com um mesmo grupo etário, em diferentes localidades do Brasil, a fim de investigar diferenças e/ou semelhanças entre a frequência dos comportamentos de risco para TA.…”
Section: Introductionunclassified